2012
DOI: 10.3201/eid1806.110948
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Laguna Negra Virus, Mato Grosso State, Brazil

Abstract: We associated Laguna Negra virus with hantavirus pulmonary syndrome in Mato Grosso State, Brazil, and a previously unidentified potential host, the Calomys callidus rodent. Genetic testing revealed homologous sequencing in specimens from 20 humans and 8 mice. Further epidemiologic studies may lead to control of HPS in Mato Grosso State.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
1
17
0
2
Order By: Relevance
“…However, it has not been tested whether all of these Akodon species act as natural reservoirs, maintaining the infection in the population by horizontal transmission, or if it is the result of spill-over infection from the primary rodent host into other species of the same genus. The same situation was observed for Laguna Negra, which was originally isolated from specimens of Calomys laucha from Paraguay (Johnson et al, 1997) and identified as the epidemiological agent that causes HPS cases in Bolivia, western Paraguay, western Brazil and northern Argentina (Johnson et al, 1997;Levis et al, 2004;Travassos da Rosa et al, 2012). Laguna Negra was also detected in rodents originally named Calomys callosus (Levis et al, 2004), later identified molecularly as C. fecundus (R. E. Gonzalez-Ittig, personal communication) and in Calomys callidus (Travassos da .…”
Section: Hantavirus -Host Relationshipssupporting
confidence: 59%
“…However, it has not been tested whether all of these Akodon species act as natural reservoirs, maintaining the infection in the population by horizontal transmission, or if it is the result of spill-over infection from the primary rodent host into other species of the same genus. The same situation was observed for Laguna Negra, which was originally isolated from specimens of Calomys laucha from Paraguay (Johnson et al, 1997) and identified as the epidemiological agent that causes HPS cases in Bolivia, western Paraguay, western Brazil and northern Argentina (Johnson et al, 1997;Levis et al, 2004;Travassos da Rosa et al, 2012). Laguna Negra was also detected in rodents originally named Calomys callosus (Levis et al, 2004), later identified molecularly as C. fecundus (R. E. Gonzalez-Ittig, personal communication) and in Calomys callidus (Travassos da .…”
Section: Hantavirus -Host Relationshipssupporting
confidence: 59%
“…Molecular identification of pathogens, their vectors, and their reservoirs is one of the expected applications of the DNA barcoding initiative. Knowledge of the exact species that is (are) carrying harmful pathogens is essential to studies of the factors leading to occurrences [ 1 , 2 ], pathogen proliferation [ 3 ], and transmission between animal vectors [ 4 6 ], as well as for epidemiological inferences as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…The circumstances of infection experienced by children from each Mato Grosso region are distinct from other ones, considering that they all have a routinely contact with wild rodents. The Central North region of Mato Grosso is devoted to agricultural activities, with extensive farms practicing direct planting and with two circulating hantavirus genotypes, Castelo dos Sonhos ( Oligoryzomys utiairitensis ) and Laguna Negra ( Calomys Callidus ) 35 , 36 .…”
Section: Discussionmentioning
confidence: 99%